Skills Ecosystems – a Solution to the Skills Problem? Experiences from the Nordics - Lundgren, Anna; Meijer, Mari Wøien (Nordic Journal of Working Life Studies, 2025)
Across countries and regions, the lack of labor, skills gaps, and skills mismatch are recurrent problems, frequently labeled as ‘the skills problem’. In this Nordic comparative study, we show how the skills problem is framed in a cross-sectoral and multi-level governance context involving education policy, labor market policy and industry and business development policy, as well as actors representing different levels of government. In five Nordic case study regions, we examine how the skills problem is framed and managed in the regional context, and how the regions work with skills analysis, skills development, and skills governance. In recent years, the concept skills ecosystems has gained increased interest. The results show that all examined Nordic regions work with basic elements from this concept, indicating an emergence of regional skills ecosystems. To conclude, the authors discuss how regional skills ecosystems have the potential to contribute to solving the skills problem.